Subacute acquired encephalopathy secondary to maternal vitamin B12 deficiency (Archives of Pediatrics of Uruguay, 2020)
Introduction: cobalamin or vitamin B12 deficiency is unusual in childhood. It may cause neurologic and hematologic symptoms of diverse severity. If not diagnosed and treated on time, it can lead to a severe clinical case of permanent neurological sequelae. The purpose of this study is to report four clinical cases of infants with subacute encephalopathy due to vitamin B12 deficiency after a maternal deficit, discuss its potential severity and emphasize the importance of preventive measures.Methods: observational study based on a review of clinical records of infants that showed clinical and laboratory criteria compatible with encephalopathy secondary to maternal vitamin B12 deficiency.Results: four infants between 7 and 15 months of age were included. They were diagnosed with vitamin B12 deficiency secondary to a maternal deficit. Clinically, they had had a symptom-free period followed by rejection of food, growth arrest, failure to thrive, irritability, apathy, regression of development, extrapyramidal movements and deceleration of cranial perimeter growth. They showed megaloblastic anemia, low serum B12 vitamin levels, hyperhomocysteinemia, and methylmalonic aciduria. They were treated with parenteral B12 vitamin and showed a favorable evolution.Discussion: vitamin B12 deficiency should always be analyzed in the differential diagnosis of infants with developmental regression, involuntary acute onset movements, seizures and apathy, especially associated with megaloblastic anemia. Due to its fairly unspecific clinical features, it high levels of suspicion and an early diagnosis are required. Treatment is simple and effective and can prevent permanent brain damage if started early.
Keywords: Encefalopatia; Deficiência de vitamina B12; Lactente